2015
DOI: 10.1021/acschemneuro.5b00282
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Mediated Increase in Nigral Tyrosine Hydroxylase Is Accompanied by Increased Nigral GFR-α1 and EAAC1 Expression in Aging Rats

Abstract: Exercise may alleviate locomotor impairment in Parkinson's disease (PD) or aging. Identifying molecular responses immediately engaged by exercise in the nigrostriatal pathway and allied tissue may reveal critical targets associated with its long-term benefits. In aging, there is loss of tyrosine hydroxylase (TH) and the glial cell line-derived neurotrophic factor (GDNF) receptor, GFR-α1, in the substantia nigra (SN). Exercise can increase GDNF expression, but its effect on GFR-α1 expression is unknown. Infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 73 publications
(260 reference statements)
2
25
0
Order By: Relevance
“…The treadmill exercise regimen followed a footshock-free exercise training regimen [ 28 , 33 ]. The exercise regimen consists of three separate phases: pre-exercise, treadmill acclimation, and treadmill exercise.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The treadmill exercise regimen followed a footshock-free exercise training regimen [ 28 , 33 ]. The exercise regimen consists of three separate phases: pre-exercise, treadmill acclimation, and treadmill exercise.…”
Section: Methodsmentioning
confidence: 99%
“…One possible mechanistic link between exercise impact on aging and locomotor function is glial cell-derived neurotrophic factor (GDNF) signaling. GDNF reduces motor impairment in aged rats and primates [ 24 , 25 ] Exercise can increase GDNF expression [ 26 , 27 ] or expression of its receptor, GFRα1 [ 28 ], and these increases are linked to increased dopamine (DA) content and tyrosine hydroxylase (TH) expression in substantia nigra (SN) [ 26 , 28 ]. However, aging may be a barrier for this exercise impact on GDNF signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that exercise improved mitochondrial function, reduced α-synuclein expression and reduced the production of pro-inflammatory factors in MPTP PD model, leading to attenuated DA denervation and motor function loss (Sung et al, 2012 ; Subramaniam and Chesselet, 2013 ; Goes et al, 2014 ; Kelly et al, 2014 ; Spielman et al, 2016 ; Jang et al, 2017 ; Koo et al, 2017a , b ). Here, we focus on neurotrophic factors (NTFs) because exercise increases NTFs in normal animals and humans and NTFs are neuroprotective and neurorestorative (Cotman et al, 2007 ; Voss et al, 2013 ; Arnold and Salvatore, 2016 ).…”
Section: Molecular Mechanisms Underlying Exercise-induced Neuroprotecmentioning
confidence: 99%
“…Besides supplying exogenous NTFs via an invasive surgery-infusion means, other methods that stimulate the production of endogenous NTFs can also be neuroprotective while avoiding the risks associated with intracranial infusion surgery. Research since the 1990's has indicated that physical activity or exercise can increase NTF production in normal animals and also in humans, although human studies are few and only serum NTFs were tested due to the difficulties in obtaining human tissue samples (Neeper et al, 1995 , 1996 ; van Praag et al, 1999 , 2005 ; Cotman and Berchtold, 2002 ; Cotman et al, 2007 ; Pereira et al, 2007 ; Voss et al, 2013 ; Coelho et al, 2014 ; Arnold and Salvatore, 2016 ; Marston et al, 2017 ).…”
Section: Molecular Mechanisms Underlying Exercise-induced Neuroprotecmentioning
confidence: 99%
“…Thus, N-acetylcysteine shows benefit via evaluation of glutathione in treatment of PD. The locomotor impairment is a common symptom in PD progression; Arnold and Salvatore indicate that short-term exercise can attenuate the locomotor impairment in aging rats via increasing nigral glial cell line-derived neurotrophic factor (GDNF) receptor, GFR- α 1, and EAAC1 expression in conjunction with increased nigral tyrosine hydroxylase expression [ 86 ]. We previously found that ceftriaxone can improve the cell viability, glutamate uptake, and GLT-1 expression in the membrane in neurotoxin MPP + -treated astrocytes [ 70 ].…”
Section: Eaats Are Potential Therapeutic Targets In Pdmentioning
confidence: 99%